Reduction of employment protection in Europe : a comparative fuzzy-set analysis - Wolfgang Ochel; Anja Rohwer (Center for Economic Studies and ifo Institute (CESifo), 2009)
Since the middle of the 1980s many European countries have reduced the strictness of their employment protection mainly by relaxing it for temporary jobs. These countries are Belgium, Denmark, Germany, Greece, Italy, the Netherlands, Portugal, Spain and Sweden. The article explores the conditions of the reduction of employment protection and takes a closer look at the combination of causal factors. It uses fuzzy-set qualitative comparative analysis (fuzzy-set QCA).
Keywords: J63; J65; J68; 330; employment protection; fuzzy-set QCA; political economy; Arbeitnehmerschutz; Arbeitsmarktflexibilisierung; Befristeter Arbeitsvertrag; Public Choice; Fuzzy Sets; Belgien; Dänemark; Deutschland; Griechenland; Italien; Niederlande; Portugal; Spanien; Schweden